Psychiatrist's adherence: a new factor in relapse prevention of schizophrenia. A randomized controlled study on relapse control through telemedicine system - Spaniel, F; Novak, T; Bankovska Motlova, L; Capkova, J; Slovakova, A; Trancik, P; Matejka, M; Höschl, C (Journal of psychiatric and mental health nursing, 2015)
ACCESSIBLE SUMMARY: Exposure to psychotic states has detrimental effects on the long-term outcome of schizophrenia and brain integrity. Therefore, improving relapse prevention is a key component of long-term management of schizophrenia. Previous studies using continuous monitoring of an individual's early signs of relapse and adopting preventative pharmacological interventions, when early signs are detected, showed promising clinical results in terms of relapse risk reduction. This 18-month multi-centre parallel randomized controlled, open label, trial with telemedicine relapse prevention programme ITAREPS failed to show superiority of maintenance plus prodrome-based targeted medication strategy over treatment as usual. The study, marked by low investigator's adherence, confirmed that absence of pharmacological intervention at early stage of prodrome, critically influenced the risk of relapse. This and previous randomized controlled trials with telemedicine programme ITAREPS suggested that substantial improvement in relapse prevention in schizophrenia is likely to be unattainable under current clinical settings. Future preventive strategies in schizophrenia would require rapid pharmacological intervention upon occurrence of subclinical prodromal symptoms that are undetectable under conventional outpatient practice. Studies with ITAREPS suggested that integration of telemedicine relapse prevention systems and visiting nurse service might together represent practical solution capable to address those requirements. ABSTRACT: The Information Technology Aided Relapse Prevention Programme in Schizophrenia (ITAREPS) presents a telemedicine solution for weekly monitoring and management of schizophrenia. This study aims to evaluate the effectiveness of the programme in reducing the number of hospitalizations during the 18-month multi-centre parallel randomized controlled, open label, trial. Outpatients with schizophrenia or schizoaffective disorder were randomized to the active (n = 74) or control group (n = 72). In the active arm, investigators increased the antipsychotic dose upon occurrence of prodrome announced by the system. Intention-to-treat analysis showed no between-group difference in the hospitalization-free survival rate [Kaplan-Meier method; hazard ratio (HR) = 1.21, 95% confidence interval (CI): 0.56-2.61, P = 0.6). In a post hoc multivariate Cox proportional hazards model, out of 13 potential predictors, only ITAREPS-related variables (number of alerts without pharmacological intervention/HR = 1.38, P = 0.042/ and patient non-adherence with ITAREPS /HR = 1.08, P = 0.009/) increased the risk of hospitalization. In this trial ITAREPS was not effective. The results in context with previous ITAREPS studies suggest non-adherence of both psychiatrists and patients as the main reasons for the failure of this preventive strategy. Tertiary prevention in schizophrenia have to be regarded a major challenge, warranting the need for implementation of strategies with more active participation of both patient and treating psychiatrist.
Keywords: dospělí; Recurrence; Telemedicine; Female; Adult; information technology; Patient Compliance; ženské pohlaví; lidé; psychotické poruchy; recidiva; relapse prevention; telemedicína; schizofrenie; adherence pacienta; sekundární prevence; Male; Secondary Prevention; psychotic disorders; Psychotic Disorders; Schizophrenia; antipsychotic medication; lidé středního věku; mužské pohlaví; hospitalizations; schizophrenia; Middle Aged; Humans